The Origins of Firm Heterogeneity: A Production Network Approach - Andrew B. Bernard; Emmanuel Dhyne; Glenn Magerman; Kalina B. Manova; Andreas Moxnes (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper quantifies the origins of firm size heterogeneity when firms are interconnected in a production network. Using the universe of buyer-supplier relationships in Belgium, the paper develops a set of stylized facts that motivate a model in which firms buy inputs from upstream suppliers and sell to downstream buyers and final demand. Larger firm size can come from high production capability, more or better buyers and suppliers, and/or better matches between buyers and suppliers. Downstream factors explain the vast majority of firm size heterogeneity. Firms with higher production capability have greater market shares among their customers, but also higher input costs and fewer customers. As a result, high production capability firms have lower sales unconditionally and higher sales conditional on their input prices. Counterfactual analysis suggests that the production network accounts for more than half of firm size dispersion. Taken together, our results suggest that multiple firm attributes underpin their success or failure, and that models with only one source of firm heterogeneity fail to capture the majority of firm size dispersion.
Keywords: F10; F12; F16; 330; production networks; productivity; firm size heterogeneity